Peningkatan Nilai-Nilai Karakter Mahasiswa Melalui KST dan Media Gambar pada Mata Kuliah Filsafat Bahasa - Agoes Hendriyanto; Nimas Permata Putri (LPPM Press, 2014)
Character education does not merely teach what is true or false, but inculcates habituationof the goodness so that the students will understand, feel, appreciate, and practice. Basedon the results of study: 1) The implementation of Cooperative Learning type Throwing Snowball, and picture media can enhance students’ character values. It can be seen from the results of the pre-test 2.33 and the ﬁnal result is 2.8; 2) The implementation ofCooperative Learning type Throwing Snowball, and picture media can enhance the abilityto think deeply and systematically of the language. It can be seen from the results of thepre-test, from 2.33 to 2.8 in the ﬁnal score; and 3) The implementation of CooperativeLearning type Throwing Snowball, and picture media can enhance the quality of learningviewed from the results of the questionnaire level of students’ satisfaction toward lecturerthat reaches 71%.